Urban analytics - Singleton, Alex; Spielman, Seth E.; Folch, David C. (SAGE, 2018)
"An explosive new interdisciplinary field of urban research. This textbook delves into the challenges and opportunities of using new and emerging forms of data to study cities. Topics explored include: data and urban computing infrastructure; sensors and human dynamics; urban modeling; agent-based modeling; [and] visualization and GIS. Over recent years, the way that data are used to understand urban systems has changed dramatically. Cities are constantly adapting to incorporate new technology, and this has fast become a key tool to analysing how cities work. Spanning current and future cities, interviews with key urban analysts, reflective questions and technical case studies, 'Urban analytics' equips the reader with a greater understanding of theory and the technical skills needed for practice." -- Zadní strana obálky
Keywords: města; urbanismus; analýza dat; cities and towns; city planning; data analysis; učebnice; textbooks